2022
DOI: 10.2147/dddt.s370114
|View full text |Cite
|
Sign up to set email alerts
|

Baicalein Inhibits the Progression and Promotes Radiosensitivity of Esophageal Squamous Cell Carcinoma by Targeting HIF-1A

Abstract: Purpose To explore the mechanism of the effect of baicalein on radioresistance of esophageal cancer, and to provide ideas for the treatment of patients with poor radiotherapy effect of esophageal cancer. Methods The glycolytic rate assay kit was used to detect the changes in glycolytic metabolism in esophageal cancer cells after treatment with baicalein, and mass spectrometry was used to detect whether baicalein could affect the level of glycolysis-related metabolites i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Notably, cells are observed to be most radio-sensitive in G2-M phase and less radio-sensitive in G1 phase. The authors concluded the potential effectiveness of baicalein to enhance radiotherapy efficacy in esophageal cancer [91] .…”
Section: Flavonoids Targeting Hif-1α To Overcome the Resistance Of Ca...mentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, cells are observed to be most radio-sensitive in G2-M phase and less radio-sensitive in G1 phase. The authors concluded the potential effectiveness of baicalein to enhance radiotherapy efficacy in esophageal cancer [91] .…”
Section: Flavonoids Targeting Hif-1α To Overcome the Resistance Of Ca...mentioning
confidence: 95%
“… Flavonoid Cancer type (resistance) Study details Effects Year Ref. Wogonin CC (cisplatin resistance) HCT116 cells in vitro ↑ sensitivity to cisplatin; ↓ HIF-1α; ↓ glycolysis-related proteins (HK2, PDHK1, LDHA); ↓ glucose uptake and lactate generation; ↓ PI3K/Akt; 2014 [14] Male BALB/c mice (tumor xenograft model – HCT116 transplanted) ↓ growth; ↓ HIF-1α via ↓ PI3K/Akt Baicalein GC (5-FU resistance) AGS cells in vitro ↓ proliferation under hypoxia; ↕ hypoxia-induced 5-FU resistance; ↓ glucose uptake and lactate under hypoxia; ↓ glycolytic-related enzymes under hypoxia (HK2, LDHA, PDK1); ↓ HIF-1α via PTEN/Akt (↓ Akt phosphorylation, ↑ PTEN protein expression) under hypoxia 2015 [30] Baicalein BC (TAM resistance) TAM-resistant BC cell lines (MCF-7TR, T-47DTR, BT-474TR, ZR-75-1TR) ↓ cell growth (OHT + baicalein vs OHT alone); ↓ cell viability, IC 50 (OHT + baicalein); ↓ clonal numbers (baicalein) and further ↓ when OHT + baicalein; ↑ apoptotic effect of OHT; ↓ HIF-1α (↓OHT-induced HIF-1α activation); ↓ aerobic glycolysis; ↕ mitochondrial dysfunction (↑ mitochondrial biogenesis); ↑ OHT-induced mitochondria-mediated ROS (↑ apoptosis) 2021 [8] Female NOD/SCID mice (MCF-7TR cells inoculated) ↑ inhibitory effects of TAM; ↓ tumor proliferation, ↑ apoptosis (TAM + baicalein vs TAM or baicalein alone); ↓ HIF-1α (baicalein or TAM + baicalein); ↑ sensitivity to TAM (↓ aerobic glycolysis and ↑ mitochondrial biosynthesis); ↓ LDHA and ↑ PGC-1α (baicalein or TAM + baicalein) Baicalein EC (radiotherapy resistance) EC cell line KYSE150 cells irradiated with 6 Gy ↓ radiotherapy resistance (↓ proliferation and not forming clones in baicalein + radiation vs radiation alone group); ↓ glycolysis (↓HIF-1α and HIF-1α PKM2); ↓ G1-related genes and proteins (regulation of CyclinD1/CDK4) 2022 [91] Oroxylin A Glioma Hypoxic model of glioma cells (human U251, rat C6, mouse GL261) in vitro ↑ sensitivity of TMZ; …”
Section: Flavonoids Targeting Hif-1α To Overcome the Resistance Of Ca...mentioning
confidence: 99%
“… 33 , 34 HIF-1α inhibitors aim to disrupt the HIF-1α pathway, thus, potentially inhibiting the adaptation of cancer cells to hypoxia and impeding their survival and proliferation. 35 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [48] found that quercetin inhibited the formation of esophageal precancerous lesions, and the inhibition was associated with decreased in ammation and esophageal cancer cell proliferation. Baicalein, a natural avonoid, not only could directly induce apoptosis, but also inhibits the progression and promotes radiosensitivity for ESCC [49,50] . Luteolin is also plant avonoid which can inhibits cell proliferation and induces cell apoptosis for human ESCC [51,52] .…”
Section: Discussionmentioning
confidence: 99%